Anti-cancer Activity of Centipeda minima Extract in Triple Negative Breast Cancer via Inhibition of AKT, NF-κB, and STAT3 Signaling Pathways - Lee, Magnolia Muk-Lan; Chan, Brandon Dow; Wong, Wing-Yan; Qu, Zhao; Chan, Man-Sum; Leung, Tsz-Wing; Lin, Yushan; Mok, Daniel Kam-Wah; Chen, Sibao; Tai, William Chi-Shing (Frontiers in Oncology, 2020)
Breast cancer is the most commonly diagnosed cancer in females worldwide. Estimates from the WHO International Agency for Research on Cancer, suggest that globally, there were around 2.1 million new breast cancer cases and 627,000 deaths due to breast cancer in 2018. Among the subtypes of breast cancer, triple negative breast cancer (TNBC) is the most aggressive, and carries the poorest prognosis, largest recurrence, and lowest survival rate. Major treatment options for TNBC patients are mainly constrained to chemotherapy, which can be accompanied by severe side effects. Therefore, development of novel and effective anti-cancer drugs for the treatment of TNBC are urgently required. Centipeda minima is a well-known traditional Chinese herbal medicine that has historically been used to treat rhinitis, sinusitis, relieve pain, and reduce swelling. Recent studies have shown that Centipeda minima exhibited efficacy against certain cancers, however, to date, no studies have been conducted on its effects in breast cancer. Here, we aimed to investigate the anti-cancer activity of the total extract of Centipeda minima (CME), and its underlying mechanism, in TNBC. In MDA-MB-231, we found that CME could significantly reduce cell viability and proliferation, induce apoptosis, and inhibit cancer cell migration and invasion, in a dose and time-dependent manner. We showed that CME may potentially act via inhibition of multiple signaling pathways, including the EGFR, PI3K/AKT/mTOR, NF-κB, and STAT3 pathways. Treatment with CME also led to downregulation of MMP-9 activity, and inhibition of metastasis in TNBC. Further, we demonstrated that CME could significantly reduce tumor burden in MDA-MB-231 xenograft mice, without any appreciable side effects. Based on our findings, CME is a promising candidate for development as a therapeutic with high efficacy against TNBC.